New Tools for Membrane Protein Research - Alguel, Yilmaz; Leung, James; Singh, Shweta; Rana, Rohini; Civiero, Laura; Alves, Claudia; Byrne, Bernadette (Current Protein and Peptide Science, 2010)
The last five years have seen a dramatic increase in the number of membrane protein structures. The vast majority of these 191 unique structures are of membrane proteins from prokaryotic sources. Whilst these have provided unprecedented insight into the mechanism of action of these important molecules our understanding of many clinically important eukaryotic membrane proteins remains limited by a lack of high resolution structural data. It is clear that novel approaches are required to facilitate the structural characterization of eukaryotic membrane proteins. Here we review some of the techniques developed recently which are having a major impact on the way in which structural studies of eukaryotic membrane proteins are being approached. Several different high throughput approaches have been designed to identify membrane proteins most suitable for structural studies. One approach is to screen large numbers of related or non-related membrane proteins using GFP fusion proteins. An alternative involves generating large numbers of mutants of a single protein with a view to obtaining a fully functional but highly stable membrane protein. These, and other novel techniques that aim to facilitate the production of membrane protein likely to yield well-diffracting crystals are described.
Keywords: amphiphiles